A Minor (<50%) Signet-Ring Cell Component Associated with Poor Prognosis in Colorectal Cancer Patients: A 26-Year Retrospective Study in China - Tan, Yinuo (PLoS One, 2015)
BACKGROUND: We performed a retrospective study to determine the cancer-specific survival of colorectal cancer patients with a component of signet-ring cells or mucin comprising < 50% of the tumor mass. METHODS: A total of 2454 patients seen in our hospital from 1985 to 2011 were retrospectively studied. The patients were divided into five groups according to type of cancer: signet-ring cell carcinoma (with > 50% signet-ring cell, n = 36), partial signet-ring cell carcinoma (with < 50% signet-ring cell, n = 28), mucinous adenocarcinoma (with > 50% mucin lacking signet-ring cell, n = 267), partial mucinous adenocarcinoma (with < 50% mucin lacking signet-ring cell, n = 145), and classic adenocarcinoma (with absence of either mucin or signet-ring cell, n = 1978). RESULTS: Patients with > 50% or < 50% signet-ring cell had the lowest 5-year survival rates (35.5% and 29.7%, respectively), followed by patients with > 50% mucin (48.8%). Patients who had partial mucinous adenocarcinoma with < 50% mucin and classic adenocarcinoma patients had the highest 5-year survival rates (64.8% and 65.3%, respectively). Stratified and multivariate analysis showed that signet-ring cell carcinoma, partial signet-ring cell carcinoma and mucinous adenocarcinoma were independent predictors of decreased survival (hazard ratio 1.699, P = 0.016; hazard ratio 2.182, P = 0.005; hazard ratio 1.532, P < 0.001; respectively), and partial mucinous adenocarcinoma was not (hazard ratio 1.137, P = 0.431). CONCLUSIONS: Patients with a component of signet-ring cells, regardless of the extent, had poor prognoses. Patients with mucinous adenocarcinoma containing >50% mucin had poor prognoses as well, whereas those with < 50% mucin had survival rates similar to those of classic adenocarcinoma patients. Therefore, in clinical practice, patients with a component of signet-ring cells, regardless of the extent, should be given significant clinical attention.